Sandstone Geomorphology of South-West Jordan, Middle East - Migoń, Piotr; Goudie, Andrew (Quaestiones Geographicae, 2014)
In the desert environment of south-west Jordan thick sequences of continental sandstones of Cambrian-Ordovician age support spectacular scenery, comparable with that of the Colorado Plateau of south-west USA or the central Sahara and similar in many aspects to the Danxia landform of southern China. Dissection of a sandstone tableland has given rise to numerous inselbergs and large mesas, rising from the sand-covered desert floor. The height of the hills varies from a few tens to 500-700 m in the Wadi Rum area, whereas their slope shapes are controlled by lithological properties of particular sandstone units. Rock walls of the sandstone inselbergs are subject to frequent rock falls and rock slides and host an impressive array of tafoni and honeycombs due to selective weathering, as well as a number of rock arches. Lithological differences within the sandstone sequence are crucial controls on the shape and evolution of rock slopes, exerting the influence via contrasting patterns of weathering and slope failures. The presence of ferruginous layers in the Umm ‘Ishrin Sandstone is of major importance and explains the fundamental morphological differences between the otherwise similar Umm ‘Ishrin and Disi sandstone units